Model Konseling Behavioral untuk Anak Penderita Attention Deficit Hyperactivity Disorder (ADHD) yang Termarjinalkan di Dunia Pendidikan - Fadhilla Yusri (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2016)
Since the last twenty years Centralization Attention Disorder is often referred to as ADHD (Attention Deficit Hyperactive Disorders). This disorder is characterized by the inability of the child to focus on something that is at hand, so that his attention span is very short time compared to other children the same age. Usually accompanied by symptoms of hyperactivity and impulsive behavior. This disorder can disrupt a child's development in terms of cognitive, behavioral, socialization and communication. There is a tendency more often in boys than girls. Epidemiologically with the incidence rate ratio of 4: 1. Academic failure is striking in children with ADHD. A child can not achieve optimal results according to his ability, or learning difficulties. Behavior modification is an approach that offered to help children with ADHD. In counseling, behavior modification can be done with the application of behavioral counseling.